ERAS protocol vs. conventional care in elective laparoscopic colorectal cancer surgery in Hatyai Hospital - Prasitvarakul, Kamales; Paekaittiwong, Danusorn; Tumviriyakul, Hathaitip; Khaimook, Araya (Frontiers in Surgery, 2025)
BackgroundEnhanced recovery after surgery (ERAS) programs and laparoscopic techniques independently reduce hospital stays and postoperative complications in patients with colorectal cancer. However, evidence regarding whether the combination of ERAS protocols with laparoscopic surgery further improves postoperative outcomes remains limited.ObjectiveThe aim of the study was to compare the postoperative hospital stay (POHS) and perioperative outcomes between patients undergoing elective laparoscopic colorectal cancer surgery under the ERAS protocol and conventional care.MethodsThis ambispective cohort study included patients who underwent elective laparoscopic colorectal surgery for colorectal adenocarcinoma at Hatyai Hospital between June 2019 and May 2023. Patients were divided into a conventional group and an ERAS group. The primary outcome was POHS. Secondary outcomes included postoperative complications and 30-day readmission.ResultsA total of 140 patients were included (70 ERAS, 70 conventional). Baseline characteristics were similar between groups, though the ERAS group had more preoperative chemoradiotherapy (CCRT) (52.9% vs. 39.4%; p = 0.002) and diverting stomas (38.6% vs. 21.4%; p = 0.042). The ERAS group had significantly shorter POHS (median 5.0 vs. 5.5 days; p < 0.001), earlier oral intake (3 vs. 4 days; p = 0.001), and earlier Jackson–Pratt (JP) drain removal (p = 0.006). There were no significant differences in postoperative complications, readmission, or mortality. Multivariate analysis identified early JP drain removal, early discontinuation of intravenous fluids, nasogastric tube avoidance, and multimodal analgesia as significant predictors of POHS ≤5 days.ConclusionERAS implementation in elective laparoscopic colorectal cancer surgery significantly reduces hospital stay without increasing complication or readmission rates. These findings support the safety and effectiveness of ERAS in a regional Thai hospital setting and advocate for broader protocol adoption.